The Effect of Public Participation Developement on the Security Feelings (Case Study of the Citizens of Yasouj City) - Mostafi Velayatinejad; Asghar Mohammadi; Seyed Naser Hejazi (توسعه اجتماعی, 2025)
The purpose of this research was to investigate the effect of the public participation development on the feeling of security. The research method was a cross-sectional-analytical survey. Using sample power method, 410 members of non-governmental organizations of Yasouj city were selected as a sample using a multi-stage cluster sampling method along with simple randomness. Data was collected using a questionnaire. To determine the validity of the questionnaire, content and construct validity were used, and Cronbach's alpha method was conducted to determine reliability. The results showed that all dimensions of the development of public participation had a significant effect on the feeling of security (P < 0.01). The variables of social, cultural, political, religious and health participation were able to predict 21.8%, 29.3%, 39.6%, 23.3% and 9.4% of the variance of citizens' sense of security, respectively. According to beta coefficients, political participation contributed the most in explaining citizens' sense of security. Further, the results showed that public participation has been able to predict 23.5, 30.9, 38.6 and 41.2 percent of the variance of the variables of financial, life, emotional and occupational security, respectively. According to the beta coefficients, among the dimensions of public participation, political participation contributed the most in explaining the feeling of financial, life and job security of citizens. Cultural participation played a role in explaining the feeling of financial security of citizens as much as the development of political participation. And finally, the variable of religious participation had the greatest prediction to the emotional security of citizens.